Teacher perceptions on the role of language assistants in bilingual physical education - Alfonso Francisco Ordóñez Dios; Beatriz Polo Recuero (Centro Universitario Cardenal Cisneros, 2020)
The inclusion of Language Assistants as teaching support in different subjects has acquired a unique value up to the point of becoming a key element in different bilingual education programs such as that of the Community of Madrid. In this Community, this leading figure has acquired such relevance and presence that it is necessary to carry out studies to describe its impact on specific subjects like Physical Education as it is one of the most selected subjects to be taught in a foreign language within the bilingual program of this region. In this research, an 'ad hoc' questionnaire has been designed, validated and administered to 87 Physical Education specialists who carried out this subject in a foreign language and co-taught with Language Assistants in bilingual public schools during 2018-19 school year. Teachers recognized, among other things, poor knowledge of Language Assistants' roles, linguistic support for teachers as their main role, the assistant's lack of knowledge of Physical Education contents as the most restricting reason for their involvement in class, and a general view of scarce help in this subject. These results should draw teachers and administration attention requiring improvements not only in their employment in class but also in the process of hiring them to maximize their potential in this subject and justify the monetary effort.